O direito marítimo e o dever fundamental de proteção do meio ambiente marinho - Obregon, Marcelo Fernando Quiroga (2017)
The present thesis investigates to what extent international treaties, considered as EXTERNAL STANDARD, governed by the joint action of the States Parties through good faith for their fulfillment, and the internal laws of a State or INTERNAL STANDARD, whose characteristic is the subordination, compulsory and coercive measures to enforce it, may require both internal and external liability, compliance with the fundamental and legal duty and application of sanctions when dealing with the preservation and protection of the marine environment in cases of pollution and Environmental damage from oil spills and other harmful substances. The Hegelian dialectic approach served as the guiding thread to understand reality through the rational and philosophical perception of the world, allowing us to understand the form of the historical development of reality, before a process incessant impulse, in which there is the proposal of a thesis that has the Claim to be true. In turn, the antithesis corresponds to the denial of the thesis and, as a result of the clash between the thesis and its antithesis, the synthesis occurs, as a new thesis that will again be confronted, that is, it is self-overcoming by confrontation. In this sense, maritime law arose in antiquity directed by the customs and customs of the societies structured at the time, as a corollary of the commercial exchange and the use of vessels as a means of transportation and commercialization of its products, promoting the assimilation and integration between heterogeneous different peoples. The investigation of the emergence of International Law of the Sea, based on the theoretical support of Eliane Maria Octaviano Martins and Jete Jane Fiorati, sought to understand the process of elaboration of regulatory norms of the uses and customs of the sea and the exploitation of its natural resources, from three International Conferences on the Law of the Sea, on the initiative of the United Nations, which served as the basis for the United Nations Convention on the Law of the Sea. This Convention regulates relations concerning the use of the sea by the Society, establishing norms, and demanding responsibilities and sanctions, together with the signatory States and other coastal and Mediterranean States. The concern of international society with the degradation of the marine environment resulting from pollution or depredation of it through a succession of incidents such as oil spills by ships during maritime transport and other forms of discharge of harmful substances dumped into the sea , Compelled the elaboration of norms and regulations, through international Conventions and ratified by the member states of the international community in a joint manner, with the elaboration of norms for the determination of civil liability for environmental damage of polluting agents, requiring the obligation to comply with Fundamental and juridical duties and the application of sanctions in order to avoid the impunity of those responsible for the criminal act. In this sense, the warnings of Lecir Maria Scalassara served as a theoretical basis for the understanding that the seas and oceans are not an inexhaustible source of resources and, above all, that their capacity to absorb pollution is limited. On this account, Hans Kelsen gives theoretical support to the need to fulfill the legal duty and the application of sanctions, from the perspective of the fundamental duty of José Casalta Nabais and Pecez-Barba Martínez, insofar as the internal and international rules stemming from Conventions relating to the protection of the marine environment are in accordance with the principles of International Environmental Law, with the legal systems in force that grant the protection and conservation of the environment a specific legislation, proper to a Democratic Rule of Law.